Implicit bias in stroke care: A recurring old problem in the rising incidence of young stroke. (March 2021) - Bhat, Aditya; Mahajan, Vipul; Wolfe, Nigel
Highlights: Stroke in younger adults is associated with a disproportionate economic and social impact. The diagnostic workup for stroke in young patients heralds unique challenges. Complicating diagnostic and management paradigms of young stroke is implicit bias. Implicit bias has been found to contribute to stroke misdiagnosis and gaps in secondary prevention. Interventions in this process have been shown to improve clinical outcomes in young stroke patients. Abstract: Stroke is a leading cause of morbidity and mortality worldwide. Although the majority of strokes affect the elderly, the incidence of stroke in young patients is on the rise. Prompt recognition of stroke symptoms and time critical therapies play a key role in management and prognosis of this condition. This is especially critical in young stroke patients, for whom delays in early recognition and treatment can result in many years of disability with associated social and financial burden. Misdiagnosis and unwarranted variation in treatment of stroke in young patients is problematic. Clinician implicit bias, the unconscious and unintentional process of judgement in healthcare decision-making, is a contributor to the short-falls in outcomes in this population. Interventions in this process have been shown to improve clinical outcomes in young stroke patients and represent an active area of study.